Tales of burning love - Erdrich, Louise 1954- (HarperCollins, 1996)
Four women share their secrets after the funeral of their ex-husband. It happens when they decide to ride back together and the car becomes stuck in a snow storm. They all agree he was a good-for-nothing, so why did they marry him? The setting is North Dakota.
Keywords: Blizzards -- Fiction; Divorced women -- Fiction; Domestic fiction.; Funeral rites and ceremonies -- Fiction; North Dakota -- Fiction; Domestic fiction